The Role of Habitat Amount and Vegetation Density for Explaining Loss of Small-Mammal Diversity in a South American Woodland Savanna - Melo, Geruza L.; Cerezer, Felipe O.; Sponchiado, Jonas; Cáceres, Nilton C. (Frontiers in Ecology and Evolution, 2022)
The focus of research and conservation in tropical regions is mainly devoted to forest ecosystems, usually neglecting the processes underlying widespread more open biomes like savannas. Here we test, for a wide range of sampled woodland sites across the South American savanna, the direct and indirect effects of habitat loss and habitat quality on the species diversity of small mammals. We quantify the direction and magnitude of the effects of habitat amount (habitat loss), patch density (tree or foliage density), and patch size (species-area effect) on species richness and composition. We also test whether the relative effect sizes of landscape and local-related metrics predict a persistence gradient from habitat specialist to generalist species across 54 sampling units. We used structural equation models (SEM) to test our predictions. After 22,032 trap-nights considering all sampled sites and 20 small mammal species identified, structural equation model explained 23.5% of the variance in small mammal species richness. Overall, we found that landscape-level metrics were more important in explaining species richness among sites, with a secondary role of patch-level metrics such as habitat quality. The direct effect of local landscape was important for explaining species richness variation, but a strong positive association between regional and local landscapes was also evidenced. Furthermore, considering the direct and indirect paths, SEM explained 46.2% of the species composition gradient. In contrast to species richness, we recorded that the combined landscape-level and patch-level metrics are crucial to determine the species composition of small mammals at savanna patches. The small mammals from South American savanna exhibit clear ecological gradients on their species richness and composition, which are driven by habitat specialist (e.g. Thrichomys fosteri, Monodelphis domestica, and Thylamys macrurus) and generalist (e.g. Didelphis albiventris, Rhipidomys macrurus, and Calomys callosus) species responses to habitat amount and/or patch density, as seen in dense-forest Neotropical biomes.